To solve for x, we will isolate the variable x by performing the necessary steps.
Starting with the given equation:
(-6/5) x - 4 = -46
First, we can get rid of the constant term in the equation by adding 4 to both sides:
(-6/5) x - 4 + 4 = -46 + 4
(-6/5) x = -42
Next, we can isolate the variable x by multiplying both sides of the equation by the reciprocal of (-6/5), which is (-5/6):
((-5/6) * (-6/5)) x = (-5/6) * (-42)
x = 35
Therefore, the solution to the equation is x = 35.
Solve for x: (-6/5) x - 4 = -46)
1 answer